Repercussões da cessão de direitos ecônomicos de atletas profissionais a pessoas físicas e jurídicas distintas das entidades de prática desportiva - Júlio César de Paula Guimarães Baía (2013)
This study emphasizes the necessity to construe the rules related to players contracts according to public policy limitations to contracts, and observing the objective good faith and other principles that underline the value of human labor. Presently, the view on players contracts focuses mostly on profit-related concerns. In light of that, we construe the constitutional principle of human dignity and propose to ban the possibility of third-party ownership, i.e., the negotiation of "economic rights" of athletes to parties other than the clubs or sports associations. The study demonstrates that third-party ownership entails treating the professional athlete as an object of law, which ought not be tolerated by a democratic state under the rule of law.